Coronavirus Disease 2019 (COVID-19) Leads to Risen Hypertension Prevalence among Type 2 Diabetes Mellitus Patients - Puspitasari, Arnindia; Rimbun; Tjempakasari, Artaria; Utomo, Dias Tiara Putri (Universitas Airlangga, 2025)
Introduction: Diabetes is the second most prevalent comorbidity of coronavirus disease 2019 (COVID-19) cases in Indonesia. Type 2 diabetes mellitus (T2DM) patients experience increased blood vessel remodeling, resulting in elevated peripheral arterial resistance. In addition to exacerbating the severity of T2DM, COVID-19 also increases hypertension risk. This study aimed to elucidate the effect of COVID-19 on hypertension prevalence among T2DM patients. Methods: This research employed an analytical observational design, specifically the case-control study design. A total of 200 datasets were extracted from medical records covering the period from May 2020 to April 2022 at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. The inclusion criteria for the study samples were T2DM patients diagnosed by a doctor, as documented in their medical records, with no previous history of hypertension. The data were analyzed using the Chi-square test at a significance level of p<0.05 to determine the effect of COVID-19 on hypertension prevalence in T2DM patients. Results: There were 100 T2DM patients without COVID-19 (30 with hypertension and 70 without hypertension) and 100 T2DM patients with COVID-19 (45 with hypertension and 55 without hypertension). The Chi-square test indicated an effect associated with COVID-19 on hypertension prevalence in T2DM patients, with p=0.028 and an odds ratio (OR) of 1.909. Conclusion: The study suggests that COVID-19 infection increases the risk of hypertension in T2DM patients. Raising awareness of the complications of hypertension is important, particularly for high-risk individuals, such as T2DM patients who have a history of COVID-19. Highlights: 1. There has been no research examining the relationship between coronavirus disease 2019 (COVID-19) and the prevalence of hypertension complications, especially in type 2 diabetes mellitus (T2DM) patients. 2. This study highlights the importance of raising awareness regarding the finding that the incidence of COVID-19 increases the prevalence of hypertension in T2DM patients.